Development and Manufacturing of Devices for the Experimental Samples Multi-element Analysis of the Composition of Matter in Real Time as Part of the Mass Spectrometer - A.V. Kosulya; V.G. Verbitskiy (Журнал нано- та електронної фізики)
The paper discloses advantages of the LSI assembly on a flexible carrier. The paper develops the topology of the flexible carrier and manufacturing of a flexible carrier. LSI samples have been composed on flexible carrier represented by a crystal attached by a dielectric on a thin flexible board with aluminium tracks located on polyimide basis. There are determined manufacturing specifications and the assembly sequence for experimental device samples. The authors constructed the experimental samples of devices for real time multi-element analysis of substances as a component of the mass-spectrometer.